In Vitro Efficacy Of Various Fungal And Bacterial Antagonists Against Rhizoctonia Solani, Causal Agent Of Damping Off Disease In Capsicun Annuum L. - ABHINITI MALHOTRA; TRIPTI AGARWAL; P. C. TRIVEDI (International Journal of Pharma and Bio Sciences, 2011)
Chilli is an important vegetable and spice crop worldwide and one of the most important vegetables in India. The chief constituent of chilli, Capsaicin has antioxidant, antibacterial and anti-cancerous properties. Rhizoctonia solani that causes damping off disease of seedlings as well as root and stem rot in young transplants, is a major soil borne pathogen of chilli. In the present study, 13 isolates of biocontrol fungi and 4 bacterial strains were evaluated against Rhizoctonia solani using Dual culture technique. Microscopic observations of fungal growth in dual cultures revealed that growth inhibition of the pathogen occurred soon after contact with the antagonist due to the efficient coiling process followed by a substantial production of hydrolytic enzymes. The results show that among the fungal species Gliocladium virens and T. harzianum (T8) are the most effective isolates at 25°C and inhibit R. solani mycelial growth by 74.82% and 73.33% respectively. Among the bacterial strains maximum growth inhibition is caused by P. fluorescens P.f.1 (73.33%) followed by P. fluorescens P.f.2 (62.22%).